A Gendered Fiscal Incidence Analysis for Ethiopia : Evidence from Individual-Level Data - Ambel, Alemayehu A.; Tesfaye, Wondimagegn M.; Yonis, Manex B. (World Bank, Washington, DC, 2022)
Using the Commitment to Equity methodology, this study investigates differences in the welfare impact of taxes and government spending on men and women in Ethiopia. It analyzes the incidence, progressivity, and pro-poorness of various taxes and transfers and their effects on income mobility, poverty, and inequality using individual-level data from the 2018/19 Ethiopia Socioeconomic Survey. The results show that the fiscal system as a whole is progressive, equalizing, and poverty-reducing. It moved about one in five individuals from one income group to another, and more women than men transitioned to a higher income group, making them relatively better off. However, some of its elements have differential effects on gender equality. Direct and indirect taxes have differential inequality-reducing and poverty-increasing effects for men and women. The inequality-reducing effects are stronger for men, whereas the poverty-increasing effects of some of them, including informal taxes and value-added taxes, are higher for women. On the transfer side, direct social protection transfers and indirect transfers, mainly spending on primary education and health services, promote gender equality better than other types of government spending.